Roles of thermostable direct hemolysin (TDH) and TDH-related hemolysin (TRH) in Vibrio parahaemolyticus - Raghunath, Pendru (Frontiers in Microbiology, 2015)
Vibrio parahaemolyticus is the leading cause of seafood borne bacterial gastroenteritis in the world, often associated with the consumption of raw or undercooked seafood. However, not all strains of V. parahaemolyticus are pathogenic. The thermostable direct haemolysin (TDH) or TDH-related haemolysin (TRH) encoded by tdh and trh genes, respectively are considered major virulence factors in V. parahaemolyticus. However, about 10% of clinical strains do not contain tdh and/or trh. Environmental isolates of V. parahaemolyticus lacking tdh and/or trh are also highly cytotoxic to human gastrointestinal cells. Even in the absence of these hemolysins, V. parahaemolyticus remains pathogenic indicating other virulence factors exist. This mini review aims at discussing the possible roles of tdh and trh genes in clinical and environmental isolates of V. parahaemolyticus.